Perioperative pembrolizumab in early-stage non-small cell lung cancer (NSCLC): safety, efficacy, and exploratory biomarker analysis - Jeff Clarke; Xiaofei Wang; Thomas Stinchcombe; Scott J Antonia; Jeffrey Crawford; Neal Ready; Konstantin H Dragnev; Lin Gu; Cameron Wood; James M Isaacs; Liliana Lyniv; Kent Weinhold; et al. (Journal for ImmunoTherapy of Cancer)
Background Our study was designed to determine the safety, efficacy, and immunological effects of perioperative pembrolizumab in early-stage NSCLC.Methods This is a single-arm phase II study of perioperative pembrolizumab in patients with untreated, clinical stage IB to IIIA NSCLC. Patients received two doses of 200 mg pembrolizumab, surgery, standard adjuvant chemotherapy, followed by four doses adjuvant pembrolizumab. The primary objective of this study was to determine surgical feasibility rate, and secondary objectives are pathological response rate, treatment adverse events, efficacy data, and exploratory analysis of biomarkers.Results 30 patients initiated perioperative pembrolizumab, and 25 completed tumor resection. At median follow-up of 59 months after surgical resection, seven patients had disease progression, while six had died representing. A 5-year progression-free survival (PFS) from time of surgery was 72.0% (56.4%–91.9%) and overall survival (OS) from time of surgery was 75.8% (60.7%–94.7%). Major pathological response (MPR) was found in seven tumors (28%) including two complete responses (4%). Across all treated patients, four receiving neoadjuvant and four receiving adjuvant pembrolizumab experienced treatment-related adverse events of grade 3 or higher with no grade 5 events. Plasma proprotein convertase subtilisin/kexin type 9 (PCSK9) levels increased across our patient cohort over time from baseline until postsurgery and remained elevated at the end of treatment. There was a significant difference between mean plasma PCSK9 levels for patients with MPR versus all other patients on study when checked postoperatively.Conclusions Perioperative pembrolizumab was safe and effective with promising MPR rate, PFS, and OS.